The Sustainable Development Goals prioritize economic growth over sustainable resource use: a critical reflection on the SDGs from a socio-ecological perspective - Eisenmenger, Nina; Pichler, Melanie; Krenmayr, Nora; Noll, Dominik; Plank, Barbara; Schalmann, Ekaterina; Wandl, Marie-Theres; Gingrich, Simone (Sustainability science, 2020)
The sustainable development goals (SDGs) were adopted in 2015, succeeding the Millennium Development Goals (MDGs). While the MDGs focused on improving well-being in the developing world, the 17 SDGs address all countries and aim at reconciling economic and social with ecological goals. We adopt a social ecology perspective and critically reflect on the SDGs’ potential for monitoring, supporting, and bringing about a transformation towards sustainability. Starting from a literature review on the SDGs, we link empirical findings from social ecology with analyses of SDG targets and indicators. First, we find that the SDGs fail to monitor absolute trends in resource use and thus prioritize economic growth over ecological integrity. Second, we discuss the contradictions between economic growth and sustainable resource use in early and late stages of industrialization processes and show that they are responsible for important trade-offs among SDG targets. Third, we analyze the transformative potential of the SDGs with a focus on the actors and institutions addressed to bring about transformative change. We find that the SDGs rely mainly on those institutions responsible for unsustainable resource use, and partly propose measures that even reinforce current trends towards less sustainability. Despite ascertaining limited transformative potential to the SDGs from an analytical perspective, we conclude by stressing the strategic relevance of the SDGs for visions, research, and practices of statt towards transformative change towards sustainability.